El ritual - Hayder, Mo; Martín Giráldez, Rubén, 1979-; Hayder, Mo. ([Madrid] : Siruela, 2016)
Police diver Flea Marley's discovery of a human hand underwater, as well as evidence that it had been recently amputated while the victim was alive, sends Flea and Detective Inspector Jack Caffery on a search for a young man who recently vanished.
Online resource; title from ePub title page (Digitalia, viewed April 14, 2017)
Keywords: Police -- England -- Fiction; Police divers -- Fiction; Bristol (England) -- Fiction; Detective and mystery fiction; Noir fiction; Psychological fiction; Electronic books